The effect of web-based blended learning echaced course on cognitive learning outcomes, scientific attitudes and learning interests of class VIII students Junior High Schools of gwamar Dobo and Negeri 1 Dobo - Meike Ocktavia Lawalata; Fredy Leiwakabessy; Alwi Smith (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2022)
ABSTRACT One of the learning problems is the integration of computer technology into learning activities that can trigger students to be able to develop learning and innovation skills, skills to use technology and information media, and be able to work and survive using life skills. The appropriate learning model that can be applied is the blended learning model that combines traditional face-to-face learning with computer-based learning with web (web enhanced) utilization. This study aims to see the effect of the web-enhanced blended learning model on cognitive learning outcomes, scientific attitudes and student learning interest in the human digestive system material. on the results of scientific attitudes and student interest in learning. The results showed that there was an effect of the web-enhanced blended learning model on cognitive learning outcomes, scientific attitudes and student interest in learning.